2022
DOI: 10.3390/molecules27144555
|View full text |Cite
|
Sign up to set email alerts
|

A New Investigation into the Molecular Mechanism of Andrographolide towards Reducing Cytokine Storm

Abstract: Cytokine storm is a condition in which the immune system produces an excessive number of inflammatory signals, which can result in organ failure and death. It is also known as cytokine release syndrome, CRS, or simply cytokine storm, and it has received a lot of attention recently because of the COVID-19 pandemic. It appears to be one of the reasons why some people experience life-threatening symptoms from COVID-19, a medical condition induced by SARS-CoV-2 infection. In situations where natural substances can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The docking energy score of stachydrine with TNF-α is −6.8 and hydrogen bonding with ARG: 332, ARG: 372 and VAL: 373 was observed [ 77 ]. The andrographolide, a labdane diterpene, binding energy with GM-CSF was −6.2 kcal/mol [ 79 ]. When the binding energy is lower than −5.0 kcal/mol, a better binding profile is shown [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The docking energy score of stachydrine with TNF-α is −6.8 and hydrogen bonding with ARG: 332, ARG: 372 and VAL: 373 was observed [ 77 ]. The andrographolide, a labdane diterpene, binding energy with GM-CSF was −6.2 kcal/mol [ 79 ]. When the binding energy is lower than −5.0 kcal/mol, a better binding profile is shown [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The cause of ARDS in COVID-19 infection is the occurrence of a cytokine storm. 4 Cytokine storm is an event of excessive release of pro-inflammatory cytokines due to an uncontrolled systemic inflammatory response. 5 Sustained cytokine storm causes tissue damage, increasing the risk of vascular hyperpermeability, multiorgan failure, and death.…”
Section: Introductionmentioning
confidence: 99%
“…Previous in silico research on the development of drugs to treat COVID-19 patients found that secondary metabolite compounds such as amentoflavone, 7-Ogalloylquercetin, kaempferitrin, and gallagic acid, a secondary flavonoid metabolite, can inhibit some proteins involved in the SARS-CoV-2 life cycle such as protease (M pro and PL pro ), RNA-dependent RNA polymerase (RdRp), and Spike protein with stable binding conformation [11]. According to other research, compounds classified as secondary metabolites, like andrographolide, have been shown to be effective in inhibiting interleukin [12]. Based on the findings of these studies, secondary metabolite compounds can inhibit the proteins involved in the SARS-CoV-2 life cycle as well as the protein that causes cytokine storm syndrome.…”
Section: Introductionmentioning
confidence: 99%